Image and Metaphor of the Sea in the Homilies on the Gospel of Saint Matthew by John Chrysostom - Szczur, Piotr (Vox Patrum, 2018)
In this article analyzes all statements of John Chrysostom from the Homilies on the Gospel of Saint Matthew containing terms: pšlagoj and q£lassa, used by our author as a designation of the sea. This analysis allowed for the extraction of few groups of sea metaphors. Chrysostom points on the sea as one of the elements of the Universe (together with heaven and earth). He describes the sea as a dangerous and uncontrollable wild element, but still subjected to Christ. The image of the sea, which – because of its enormity – is beyond other elements of the Universe, is used by Golden Tongued to describe immensity and commonness. And the reference to sea threats (winds, sea currents, storms, shallows) inclines him to describe human life as a sailing across the rough sea.